Dosimetric performance of cone beam CT-guided adaptive carbon-ion radiotherapy with daily replanning for pancreatic cancer - Klassen, Lukas Fabrizio; Hirashima, Hideaki; Iramina, Hiraku; Iwai, Takahiro; Yoshimura, Michio; Tanaka, Hiroki; Mizowaki, Takashi; Nakamura, Mitsuhiro (Physica medica, 2025)
Purpose - We investigated whether an ultra-hypofractionated carbon-ion radiotherapy (CIRT) protocol for pancreatic cancer (PC) could produce satisfactory dosimetric results with or without cone-beam CT-guided adaptive replanning and explored the potential dosimetric advantages of the adapted protocol. - Methods - Eleven PC patients who underwent CBCT-guided online adaptive photon radiotherapy were selected. Data were imported into a CIRT treatment planning software to develop new plans for an ultra-hypofractionated CIRT protocol. Prescriptions and constraints were recalculated for a five-fraction schedule using a linear quadratic model for organs-at-risk (OARs) and targets, respectively. The biologically effective dose-equivalent prescribed dose was set at 43.2 Gy (relative biological effectiveness [RBE]). Each day, a synthetic CT (SCT) was generated from the planning CT (PCT) with the daily CBCT. A reference plan based on the PCT was compared to an adapted plan based on the SCT. Deformable image registration was used to allow summation of the daily doses. - Results - The adapted plans met the clinical goals, whereas the reference plans exceeded the constraints in 27 % (stomach), 53 % (duodenum), and 31 % (small bowel) of the fractions. The adapted plans notably decreased V35.5 Gy[RBE] for all gastrointestinal OARs, while significantly enhancing the gross tumor volume (GTV) D95% and planning target volume (PTV) D90%. The accumulated doses showed significant improvements in the duodenum V35.5 Gy[RBE], GTV D95%, and PTV D90%. - Conclusion - CBCT-guided adaptive CIRT for PC demonstrated favorable dosimetric results, notably enhancing the sparing of OARs and ensuring superior target coverage compared with non-adaptive CIRT protocols.